A biopsychosocial framework to guide interdisciplinary research on biathlon performance - Heinrich, A.; Stoll, O.; Cañal-Bruland, R. (Frontiers in Psychology, 2021)
Biathlon is a unique combination of two challenging and remarkably different tasks: cross-country skiing in free technique and rifle shooting in either prone or standing position. Over the past few decades, a growing body of biathlon-specific research considerably improved our understanding of the factors determining biathlon performance (for a review, see Laaksonen et al., 2018). This includes biological aspects of biathlon performance, comprising physiological parameters (e.g., Rundell and Bacharach, 1995; Stoeggl et al., 2015; Laaksonen et al., 2020) as well as biomechanical and motor control factors such as postural control, rifle stability, shoulder force, and triggering or aiming strategies (e.g., Groslambert et al., 1999; Baca and Kornfeind, 2012; Sattlecker et al., 2014; Köykkä et al., 2020). In addition, another branch of research focuses on psychological factors that influence performance, including the role of attentional processes (e.g., Gallicchio et al., 2016; Luchsinger et al., 2016; Heinrich et al., 2020), dealing with psychological pressure (e.g., Vickers and Williams, 2007; Lindner, 2017) and the effectiveness of psychological interventions (e.g., Groslambert et al., 2003; Laaksonen et al., 2011). However, with only one exception (Harb-Wu and Krumer, 2019), biathlon-specific research has largely overlooked the degree to which social context factors may impact biathlon performance. Here, we advocate a holistic approach to gain a more complete understanding of the factors contributing to biathlon performance. Admitting to the fact that biological determinants, psychological factors, and social context never occur in isolation, but instead need to be considered in conjunction, we propose a biopsychosocial framework to guide future research efforts into biathlon performance. This integrative, interdisciplinary, and holistic approach to examine biathlon performance is illustrated in Figure 1. Originally, biopsychosocial approaches were developed in the area of medicine and psychiatry to address limitations of the traditional biomedical model and generally aim at considering behavioral, psychological, and social dimensions when trying to understand a person`s condition (Engel, 1977, 1997). Nowadays, biopsychosocial models have stepped out of their original scope and are widely used, for instance, to explain arousal regulation (Blascovich and Tomaka, 1996) or to examine stress in adolescence (Rith-Najarian et al., 2014). The application of biopsychosocial models in sport is scarce and mainly limited to the field of injuries or pain (e.g., von Rosen et al., 2017; Bumann et al., 2020). Before outlining the specific steps that need to be taken to realize a research agenda in biathlon guided by the proposed biopsychosocial framework, we shortly summarize evidence stemming from research focusing on isolated, that is, biological, psychological, and social aspects of the framework